2020
DOI: 10.1016/j.yebeh.2020.107211
|View full text |Cite
|
Sign up to set email alerts
|

Emergency implementation of telemedicine for epilepsy in Spain: Results of a survey during SARS-CoV-2 pandemic

Abstract: Teleneurology in Spain had not been implemented so far in clinical practice, except in urgent patients with stroke. Telemedicine was hardly used in epilepsy, and patients and neurologists usually preferred onsite visits. Our goal was to study impressions of adult and pediatric epileptologists about the use of telemedicine after emergent implementation during the new coronavirus 2019 (COVID-19) pandemic. Methods: An online survey was sent to the members of the Spanish Epilepsy Society and the members of the Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 13 publications
2
49
0
Order By: Relevance
“…One observational comparative study confirmed that PWE showed more psychological distress than healthy controls, and they spent significantly more time following the COVID-19 outbreak news [13]. Finally, four studies showed that telemedicine may improve access to specialized care for PWE in these difficult times [10,[20][21][22]. The development of an epilepsy electronic patient portal may promote improved patient-clinician partnerships and facilitate patient self-management [23] 1.2.…”
Section: Resultsmentioning
confidence: 99%
“…One observational comparative study confirmed that PWE showed more psychological distress than healthy controls, and they spent significantly more time following the COVID-19 outbreak news [13]. Finally, four studies showed that telemedicine may improve access to specialized care for PWE in these difficult times [10,[20][21][22]. The development of an epilepsy electronic patient portal may promote improved patient-clinician partnerships and facilitate patient self-management [23] 1.2.…”
Section: Resultsmentioning
confidence: 99%
“…. Considering this last aspect, the SARS-CoV-2 crisis has obliged physicians to adopt telemedicine in a very accelerated way to maintain essential care for patients with epilepsy during the pandemic [11,12]. On the other hand, the discussion about SUDEP and the possibility of the occurrence of a greater number of cases of premature death among individuals with epilepsy has not been receiving special attention during application of telehealth.…”
mentioning
confidence: 99%
“…Thus, an interesting recent study evaluated experiences of adult and pediatric epileptologists about the use of telemedicine after emergent implementation during the new SARS-CoV-2 pandemic. In brief, the authors clearly demonstrated that certain topics, such as SUDEP, were felt to be more appropriate to discuss face to face [11].…”
mentioning
confidence: 99%
See 2 more Smart Citations